The role of extensive listening in english foreign language (EFL) class - Saputra, Yuyus; Fatimah, Asri Siti ((JELE) Journal Of English Language and Education, 2018)
Aims of the research are (1) to know how extensive listening applied in EFL classroom, (2) To know the students’ reflection dealing with EL’s role in developing their listening comprehension ability. Method of the research is a reflective learning by investigating students’ reflection in the process of learning in extensive listening and its role for their listening comprehension ability. Data taken from students’ writing journal in ten meetings during teaching and learning practice. Besides, interview was used to confront the diaries and their experiences during learning listening in EFL classroom